(untitled) (Contemporary Issues on Indonesian Human Rights Law and Policy, 2025)
This paper examines the state of human rights education in Indonesia, focusing on the gap between policy frameworks and actual practice in schools and universities. While human rights education is enshrined in national policies and the Indonesian Constitution, its implementation remains inconsistent across different educational institutions and regions. Using a combination of policy analysis, fieldwork, and interviews with educators, students, and human rights experts, the study investigates how human rights topics are integrated into the national curriculum, teaching methodologies, and extracurricular activities. The research identifies key challenges such as insufficient teacher training, lack of resources, and resistance from conservative groups. The paper further explores the role of civil society organizations in supplementing state-led education programs and the impact of local culture and politics on the teaching of human rights. The findings reveal that while there is growing awareness of human rights in Indonesia, the education system’s capacity to instill a human rights culture remains limited. The study concludes by suggesting improvements, including curriculum reforms, better teacher training, and greater collaboration between the government and civil society in advancing human rights education.